Models of Pb distribution and uptake in inundated paddy and maize cropping systems - Nopriani, Leny Sri; Prayogo, Cahyo; Soemarno, Soemarno; Atikah, Atikah; Kusuma, Zaenal (Journal of Degraded and Mining Lands Management, 2023)
High-traffic highway crossing agricultural fields impacts the quality of food crops grown on Vertisol agricultural fields in Pasuruan. Lead (Pb) released from the exhaust of motor vehicles into the air can eventually enter the soil and be absorbed by plants. This study aimed to examine the effect of Pb from exhaust motor vehicles emission on the Pb status and its behavior in soil, water, and plants. The study was initiated by conducting a survey to determine the sampling locations in selected inundated paddy and maize cropping systems. A stratified random sampling method was used to collect soil, water, and plant samples. The soil of the study area is dominated by Vertisol, with clay content ranging from 54% to 76%. The soil attributes a high cation exchange capacity ranging from 80.53 meq 100 g-1 to 93.57 meq 100 g-1. Pb emitted from 2,913,000 vehicles within four months period that entered the agricultural field was not absorbed by paddy and maize crops. Pb entered the soil in the adsorbed form, and no Pb was observed in the soluble form, so it was not absorbed by the roots. In the paddy field, the total Pb of 84.33% was influenced by pollutant distance. Likewise, in the maize field, 83.18% of total Pb was influenced by pollutant distance. The far the pollutant distance from the agricultural field, the lower its total Pb. Paddy field water is adsorbed onto the colloidal clay, which is dispersed due to inundation and sloughing of the paddy, moving with the clay and then dissolved in the water flow.